2021
DOI: 10.1111/cen.14439
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone score and bone mineral density in patients with long‐term controlled acromegaly

Abstract: Objective Acromegaly is associated with increased vertebral fracture (VFs) risk not correlated to bone mineral density (BMD). Trabecular bone score (TBS), related to bone microarchitecture, provides information on bone strength. This cross‐sectional study considered the usefulness of TBS and BMD to assess bone status in long‐term controlled acromegalic patients. Design, patients, measurements 26 acromegaly patients (14 female and 12 males) were included in the study. A further 117 subjects were recruited as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 34 publications
2
27
0
Order By: Relevance
“…In the present study, we found that TBS values were lower in acromegalic patients compared to age, BMI, and sex-matched healthy controls, while no significant differences were observed in BMD values between the two groups, both at lumbar and femoral sites. These data are in line with the results reported by other authors, although some studies did not find significant differences in TBS values between patients and matched controls [ 23 , 41 , 42 , 43 , 45 , 46 , 47 ]. Furthermore, we observed that both BMD and TBS values were significantly lower in hypogonadal patients compared to the eugonadal ones, thus confirming the pivotal role of gonadal status on both bone density and quality in acromegaly [ 6 , 40 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the present study, we found that TBS values were lower in acromegalic patients compared to age, BMI, and sex-matched healthy controls, while no significant differences were observed in BMD values between the two groups, both at lumbar and femoral sites. These data are in line with the results reported by other authors, although some studies did not find significant differences in TBS values between patients and matched controls [ 23 , 41 , 42 , 43 , 45 , 46 , 47 ]. Furthermore, we observed that both BMD and TBS values were significantly lower in hypogonadal patients compared to the eugonadal ones, thus confirming the pivotal role of gonadal status on both bone density and quality in acromegaly [ 6 , 40 ].…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous findings, we observed a significant inverse correlation between TBS values and age in acromegalic patients, although this correlation was not found in the control group [ 23 , 37 , 43 , 46 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Correspondingly, Calatayud et al. revealed significantly lower TBS values in controlled acromegalic patients, despite no difference in LS BMD ( 31 ). In another study, Goldang et al.…”
Section: Discussionmentioning
confidence: 96%
“…Using impact micro-indentation, Malgo et al illustrated that acromegaly patients in remission have impaired cortical bone strength relative to healthy controls (21). Furthermore, the trabecular bone score (TBS) of acromegaly patients continues to decline after the disease had been rigorously controlled (22,23). Therefore, we should pay more attention to evaluating bone microstructure and preventing fractures in acromegaly patients, even if the disease had been satisfactorily controlled.…”
Section: Discussionmentioning
confidence: 99%